2020
DOI: 10.3389/fnins.2020.00688
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function Declines Following Orthostatic Stress in Adults With Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS)

Abstract: Introduction Orthostatic intolerance (OI) is common among individuals with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). Cognitive dysfunction has been demonstrated during head-up tilt testing (HUT) in those with ME/CFS: worse scores on cognitive tests occur with increasing tilt angles and increasing complexity of the cognitive challenge. The aim of our study was to determine whether cognitive impairment persists after completion of HUT. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
5
7
0
Order By: Relevance
“…The increased symptoms were associated with a statistically and clinically significant decrease in CBF compared to HC. Extending these findings, we show that working memory function, as assessed by the n-back test, decreased immediately after HUT (35). Furthermore, we show a decrease in pressure pain thresholds (PPT) immediately after orthostatic stress similar to PPT changes in ME/CFS patients after an exercise stressor (36).…”
Section: Discussionsupporting
confidence: 74%
“…The increased symptoms were associated with a statistically and clinically significant decrease in CBF compared to HC. Extending these findings, we show that working memory function, as assessed by the n-back test, decreased immediately after HUT (35). Furthermore, we show a decrease in pressure pain thresholds (PPT) immediately after orthostatic stress similar to PPT changes in ME/CFS patients after an exercise stressor (36).…”
Section: Discussionsupporting
confidence: 74%
“…To date, the etiology and pathophysiology of ME/CFS is still unresolved, but there is ample evidence for autonomic and vascular dysregulation [4][5][6]. Hypoperfusion of muscles and impaired cerebral blood flow upon exertion are considered as key mechanisms for fatigue muscle pain, PEM and impaired cognition [6][7][8][9][10] (Fig. 1).…”
mentioning
confidence: 99%
“…Previous studies have indicated the relationship between autonomic disturbance and cognitive dysfunction in ME/CFS [6]. Moreover, a decline in cognitive function has been noted after orthostatic stress, which is a provocative test for autonomic nervous system responsiveness [7]. Autonomic nervous system dysfunction is one of the most widely described parts of ME/CFS pathomechanisms [8].…”
Section: Introductionmentioning
confidence: 99%
“…Autonomic nervous system dysfunction is one of the most widely described parts of ME/CFS pathomechanisms [8]. Autonomic dysfunction could be related to a decrease in processing speed in ME/CFS [7]. Autonomic nervous system function was measured non-invasively using heart rate variability (HRV) as an indicator of cardiac autonomic innervation [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation